2017
DOI: 10.1097/ta.0000000000001466
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation profiles as predictors of symptomatic venous thromboembolism after trauma

Abstract: Background Reliable biomarkers predictive of venous thromboembolism (VTE) after acute trauma are uncertain. The objective of the study was to identify risk factors for symptomatic VTE after trauma, including individual plasma coagulome characteristics as reflected by thrombin generation. Methods In a prospective, case-cohort study, trauma patients were enrolled over the 4.5 year period, 2011–2015. Blood was collected by venipuncture into 3.2% trisodium citrate at 0, 6, 12, 24 and 72 hours after injury, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 29 publications
3
61
0
Order By: Relevance
“…The main advantage of this procoagulant mechanism in terms of survival could be to counterbalance the effect of coagulation factors depletion and aPC-mediated fibrinolysis. However, thrombosis is the price to pay to lower mortality [24]: a recent publication concluded that a procoagulant phenotype was a predictor of symptomatic venous thromboembolism after trauma [48]. These observations are consistent with the fact that, after several days, patients with ATC present higher mortality rates despite the restoration of normal blood pressure.…”
Section: Discussionmentioning
confidence: 61%
“…The main advantage of this procoagulant mechanism in terms of survival could be to counterbalance the effect of coagulation factors depletion and aPC-mediated fibrinolysis. However, thrombosis is the price to pay to lower mortality [24]: a recent publication concluded that a procoagulant phenotype was a predictor of symptomatic venous thromboembolism after trauma [48]. These observations are consistent with the fact that, after several days, patients with ATC present higher mortality rates despite the restoration of normal blood pressure.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, trauma patients exhibit increased thrombin generation in comparison with healthy controls [26,[30][31][32]. Importantly, patients hospitalized after trauma encounter a substantially elevated risk of venous thromboembolism, and elevated thrombin generation has been shown to be an independent predictor for venous thromboembolic events in this patient cohort [33,34].…”
Section: Discussionmentioning
confidence: 92%
“…Park et al identified CAT lag time and time to thrombin peak as risk factors for development of venous thromboembolism in patients after acute trauma, HR 1.66 (1.06, 2.60) p < .028 and HR 2.02 (1.45, 2.80) p < .001, respectively. They conclude that CAT is potentially a useful clinical tool in predicting the occurrence of VTE after injury . CAT is advantageous because it is not confounded by cellular components of blood and is specific for thrombin production.…”
Section: Discussionmentioning
confidence: 99%